Problem-based learning in developing students’ communicative skills and creativity in teaching English for specific purposes - Jolita Šliogerienė; Irena Darginavičienė; Jelena Suchanova; Dalia Gulbinskienė; Viktorija Jakučionytė (Creativity Studies)
Tertiary education uses a variety of teaching methods to cater for different learning styles, encourage critical thinking, and prepare students for real-world challenges. Common methods include lectures, seminars, independent study, and collaborative learning. This diversity reflects the complexity of higher education and helps to create a dynamic learning environment that fosters lifelong learning and critical thinking skills. Problem-based learning, a prominent teaching method, focuses students on an inquiry-based approach, presenting them with real-life problems that require the application of knowledge, critical thinking, creative approach, and collaboration. Problem-based learning is very effective in teaching English for specific purposes at tertiary level because it involves students in projects that require the use of the target language, thus enhancing language acquisition and fostering communicative skills. This method benefits students by promoting active learning, improving communication, encouraging creativity, and developing problem-solving skills. A study at Vilnius Gediminas Technical University, Lithuania, involving students from creative and technical fields, found that most students found problem-based learning beneficial, although creativity students were more enthusiastic. The results suggest that while problem-based learning improves understanding of both theoretical and practical aspects of study programmes, technical students are more sceptical about the effectiveness of problem-based learning. Despite some negative attitudes on the part of some students, problem-based learning remains a valuable tool in English for specific purposes education, supporting the development of language and professional skills.